Towards High Power High Energy Aqueous Sodium‐Ion Batteries: The NaTi2(PO4)3/Na0.44MnO2 System. Issue 3 (18th October 2012) - Li, Zheng; Young, David; Xiang, Kai; Carter, W. Craig; Chiang, Yet‐Ming
<x xml:space="preserve">Abstract</x> Ultrafast rate capability (>100 C current rates) and superior high‐rate cycling stability (>1500 cycles) in aqueous NaTi2(PO4)3/Na0.44MnO2 cells are demonstrated. Aqueous NaTi2(PO4)3/Na0.44MnO2 cell may be a candidate for safe, low cost, high power storage systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>